Simultaneous Local Elections in Indonesia: More Power for Incumbents? - Arifianto, Alexander R. (2016)
Indonesia held its first simultaneous local executive elections (Pilkada Serentak) on 9 December 2015. While administrative efficiency was the primary rationale for the simultaneous elections, structurally it may lead to greater power consolidation among incumbent executives, especially those with linkages to local political dynasties.